BANKRUPTCY PREDICTION MODELS: PRELIMINARY THOUGHTS ON THE DETERMINATION OF PARAMETERS FOR THE EVALUATION OF EFFECTIVENESS AND EFFICIENCY - Cestari, Greta; Risaliti, Gianluca; Pierotti, Mariarita (European Scientific Journal, ESJ, 2013)
﻿From initial developments (Beaver, 1966; Altman, 1968), the interest of experts, academics and others regarding models of bankruptcy prediction, has intensified, also in the light of the recent global economic-financial crisis. To date research in this field has mainly concentrated on the development of an instrument that has a higher level of reliability. Particular attention, has therefore been paid to the fine-tuning of the logical-technical system of models and proven efficiency, in terms of overall accuracy and proportional impact of errors made according to type. Nonetheless, one aspect that has not been explored in full in this field is that of accessibility of models that require the analysis of factors that affect usability of these instruments in an operational field. The analysis perspective is that of the user, therefore, over and above the diagnostic accuracy test, specific importance must be given to the implications which the adoption of the model can have on the user’s organisation and the costs that are involved with the use thereof. The diagnostic instrument can be effectively and profitably used only if these implications are sustainable for the specific user. This article aims at identifying the parameters that can measure efficiency, in terms of diagnostic reliability and speed, and effectiveness, in terms of organisational and economic sustainability, of prediction instruments. This objective has been pursued with an in-depth analysis of existing literature in matters of bankruptcy prediction models.